PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP RETURN ON EQUITY (ROE) PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2002 – 2011 - B11108039, Gunawan Raharjo (Jurnal Manajemen Update, 2014)
Ratio commonly used to measure the liquidity pretty much, but here only the ratios discussed above are considered to represent the other ratios are the ratio of current assets and current liabilities (CR). Liquidity is a problem related to a company's ability to issue obligations to be fulfilled immediately financialnya that. A company that has liquid instruments such that it is able to meet all obligations must be fulfilled immediately financialnya which, it is said that the company is illiquid Solvency indicates a company's ability to pay off all debts both long-term debt and short-term debt when the company liquidated. Ratio commonly used to measure solvency quite a lot, but will be discussed here only two ratios are considered to represent the other ratios are the ratio of total debt to total assets (DAR) and total debt to total equity (DER). Return On Equity (ROE) is a measure of corporate performance that illustrates how much the rate of return or the level of prosperity that can be produced by the company for its shareholders. In general, changes in ROE is strongly influenced by changes in the level of solvency of the company in this case the ratio of total debt to total assets and total debt to total equity of the company. By using multiple linear regression analysis method, in this study will be analyzed whether there was a significant effect between CR, DAR and DER on ROE. The study was conducted by taking a sample of five mining companies, namely PT. Bumi Resources Tbk, PT. Aneka Tambang Tbk, PT. International Nickel Indonesia Tbk, PT. Timah and Bukit Asam Coal Mine (Persero) Tbk of many companies engaged in the mining sector are listed in the Indonesia Stock Exchange (IDX) during the period 2002-2011. Results of the analysis showed that CR, DAR and DER simultaneously or partially no effect on ROE. Keywords: Liquidity, Solvency and Return On Equity (ROE)